Penerapan Etika Profesi Kepala Sekolah di Mi Tarbiyatul Islam 01 - Astuti Darmiyanti; Saprialman Saprialman; Nursyifa Nursyifa (Peneliti.net, 2023)
Ethics is an important requirement for all existing professions so as not to take actions that deviate from the law. Ethics are life values and norms and laws that govern human behavior. The rationale underlying the preparation of professional ethics is the need for the profession regarding public trust in the quality of services provided by the profession, regardless of the members of the profession who provide the service. The application of professional ethics which is part of professional ethics relates to how they must carry out their profession in a professional manner so that accepted by society. With the application of professional ethics it is expected that professionals can work as well as possible, and can be accountable for the tasks carried out in terms of job demands. The school principal as a leader is directly a real example in the activities of his subordinates. If you want good subordinates/employees, then the principal the school first sets a good example too. A good school principal should always comply with the code of ethics of the profession. As an educated human being, of course the principal is expected to always uphold the dignity of the principal's good name.